Happiness in texting times - Hevey, David; Hand, Karen; MacLachlan, Malcolm (Frontiers in Psychology, 2015)
Assessing national levels of happiness has become an important research and policy issue in recent years. We examined happiness and satisfaction in Ireland using phone text messaging to collect large-scale longitudinal data from 3,093 members of the general Irish population. For six consecutive weeks participants’ happiness and satisfaction levels were assessed. For four consecutive weeks (weeks 2 to 5) a different random third of the sample got feedback on the previous week's mean happiness and satisfaction ratings. Text messaging proved a feasible means of assessing happiness and satisfaction, with almost three quarters (73%) of participants completing all assessments. Those who received feedback on the previous week’s mean ratings were eight times more likely to complete the subsequent assessments than those not receiving feedback. Providing such feedback data on mean levels of happiness and satisfaction did not systematically bias subsequent ratings either towards or away from these normative anchors. Texting is a simple and effective means to collect population level happiness and satisfaction data.